Role of biological, social and psychological factors in determining the menarche age: a multi-centered cross-sectional study in Karachi, Pakistan - Tarar, Hamna Mukhtar; Jameel, Khadija; Shahzad, Abeer; Hameed, Shibrah; Oduoye, Malik Olatunde; Fudda, Kiran Ismail (International Journal Of Community Medicine And Public Health, 2025)
Background: Menarche marks the beginning of the menstrual cycle, reflecting a complex interplay of biological, environmental, nutritional and socio-economic factors that contribute to variations in age at menarche. To determine the impact of physical and psychosocial factors on the age of menarche in girls from different socioeconomic backgrounds in Karachi, Pakistan. Methods: A cross-sectional descriptive study was conducted among 305 female students aged 9 to 15 years from four different schools in urban and rural areas of Karachi district, Pakistan in 2022. Subjects who had not yet menstruated were excluded. Bilingual questionnaires were used in the study to record the responses. Height and weight were measured using calibrated instruments. The psychological stress levels were measured using APA LEVEL 2-anxiety-child aged 11-17 (Promis emotional distress -Pediatric Item bank). SPSS version 25 was used to find a correlation between the age of menarche with different biological, social and psychological factors. Results: The mean age of menarche was 11.9±1.09 years. The study showed a significant correlation between body mass index and the father’s occupation was found (p<0.05). Presence, education, occupation, the combined income of both parents, number of siblings and female siblings, physical activity, diet, abuse, home environment, psychological and physical effect of COVID-19 lockdown and anxiety levels did not show any significant correlation with age of menarche. Conclusions: This study supports the significant influence of body mass index and the father’s occupation on the age of menarche.